Sanctions Against Criminal Acts of Gambling on Skill Games Shooting Fish in the Legal Area of the Medan District Court - Ongku Sapna Fella Hasibuan; Yasmirah Mandasari Saragih; Sumarno Sumarno; M. Yusuf Afandi; Efraim Abigail Bukit (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
One of the gambling cases that was decided through the Medan District Court was the fish shooting gambling case, decision number 2452/Pid.B/2021/PN Mdn.Currently, many fish shooting games are found as gambling games in the community. The consequences of shooting fish gambling bring things that are not good financially and disrupt people's mindsets. The formulation of the problem that is made is How are the Sanctions in the Crime of Gambling Fish Shooting Game in the Medan District Court?, How is the Review of Criminal Law Against the Crime of Gambling Fish Shooting Game? This research uses normative research methods in the form of primary and secondary data sources which are then analyzed using descriptive analysis techniques with a deductive mindset. The results of the research are first, the decision of the District Court number 2452/Pid.B/2021/PN Mdn regarding the crime of gambling fish shooting agility games based on Article 303 Bis paragraph (1) 1 of the Criminal Code, which is to impose a prison sentence of 1 (one) year. ) year. Followed by the testimony of witnesses, defendants, evidence and considering things that are aggravating and mitigating for the defendant when determining the sentence of criminal sanctions.